A study to explore nurses views on where adolescents and young adults with cancer should be treated - Larter, Stephanie (2012)
It is apparent from the literature and from discussions with staff nurses that the treatment location of adolescents and young adults with cancer is a hot topic which is constantly evolving. The aim of this qualitative study was to gain an insight into nurse’s views on the nursing culture, care needs of AYA’s, treatment location and organisation of care associated with the age group. This was achieved by 11 semi-structured interviews with 6 adult trained nurses and 5 paediatric trained nurses. All interviews were transcribed and analysed using thematic content analysis. It was found that nursing staff face many challenges nursing AYA’s in the adult and paediatric environment, experiencing lack of training and support, combined with the lack of facilities that AYA’s need for achievement of holistic care. Overall the adult setting faced more significant barriers than the paediatric in achieving adolescent’s needs.